Pengaruh Penyelenggaraan Event Kebudayaan terhadap Keputusan Berkunjung ke Kota Palembang - Muhammad Ibnu Fajar; M. Syahirman Yusi; Desloehal Djumrianti (Politeknik Negeri Sriwijaya, 2021)
The purpose of this research was to determine how the influence of organizing a cultural event called Sriwijaya Festival, on the decision to visit Palembang City through variables of uniqueness, hospitality, symbolism, festive spirit, theme and authenticity. The method used is descriptive quantitative. The results showed that the independent variable simultaneously had a positive and significant effect on the decision to go to Palembang City. Partially, hospitality and themes have a significant and positive effect on the decision to visit Palembang City, while symbolism and authenticity have no significant and negative effect on the decision-making variables to visit Palembang City. As well as the uniqueness and festive atmosphere has no significant and positive effect on the decision to visit Palembang City. The magnitude of the influence of holding cultural events on the decision to visit Palembang City based on the results of the determination coefficient test is 36.2% and the remaining 63.8% is influenced by other factors which are not discussed in this study.